Enhanced Competent Hydrocast With Power Consumption For Communication Void Avoidance In Uwsn - P.Sathya, Dr. P.Sengottuvelan (International Journal of Advanced Science and Technology, 2020)
Earth is largely secured by water. In Underwater Wireless Sensor Networks, conventional large, expensive, singular ocean monitoring equipments are supplanted by generally little and more affordable underwater sensor nodes that can speak with one another by means of acoustic signs. In existing paper, bypassing void region, power adjustment, and depth adjustment methods are used to avoid void nodes in the network. However, bypassing void avoidance method induces excessively control overheads. To reduce the control overhead, power adjustment or energy change method was proposed.  So in this paper we proposed Enhanced Competent Hydrocast with Power Consumption (ECHPC) for communication void Avoidance.